Giant cystic lymphangioma in the mesoileum: A case report and literature review - Liu, Ling; Ke, Ge; Shen, Wei-Min; Jia, Chang-Ku (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Liu L, Ge K, Shen WM, Jia CK. Giant cystic lymphangioma in the mesoileum: A case report and literature review. Turk J Gastroenterol 2020; 31(8): 603-6.